Molecular mechanism of Arp2/3 complex activation by nucleation-promoting factors and an actin monomer - Sahithya Sridharan Iyer; Jiangbo Wu; Thomas D. Pollard; Gregory A. Voth (Proceedings of the National Academy of Sciences, 2025)
Arp (actin-related protein) 2/3 complex nucleates actin filament branches on the sides of preexisting actin filaments during cell and organelle movements. We used computer simulations of mammalian Arp2/3 complex to address fundamental questions about the mechanism. Metadynamics and umbrella free energy sampling simulations of the pathway revealed that a clash between the D-loop of Arp2 and Arp3 produces an energy barrier of 20 ± 6 kcal/mol between the inactive splayed and active short-pitch conformations of Arp2/3 complex. Atomistic molecular dynamics simulations showed that binding the CA motif of the nucleation-promoting factor Neuronal Wiskott-Aldrich Syndrome Protein (N-WASp) to inactive, splayed Arp2/3 complex shifts it toward the short-pitch active conformation and opens a binding site for an actin monomer on Arp3. Other simulations showed that this actin monomer stabilizes a transition state of Arp2/3 complex. These observations together with prior experimental work provide insights required to propose a physically grounded pathway for actin filament branch formation.